Genome-wide identification and expression analysis of the WRKY transcription factors related to sesquiterpenes biosynthesis in Atractylodes lancea - Liang, Hua; Liu, Weiwei; Zhao, Zhiqiang; Li, Yaqian; Zha, Liangping (Frontiers in Genetics, 2025)
IntroductionAtractylodes lancea (Thunb.) DC., a widely utilized herb in traditional Chinese medicine, contains sesquiterpenoids and polyacetylenes as its primary bioactive components. The WRKY gene family plays a critical role in regulating various biological processes in plants. However, the molecular mechanism underlying AlWRKY regulation of terpenoid synthesis unclear.MethodsThe AlWRKY gene family members were identified through bioinformatics approaches. Gene structures, motifs, and phylogenetic relationships were analyzed. Subsequently, their expression profiles across different geographical origins were investigated using transcriptome data. Furthermore, preliminary validation was performed via methyl jasmonate treatment and molecular docking, with a focus on the AlWRKY20 and AlWRKY37 genes.ResultsIn this study, 65 AlWRKY genes with conserved domains were identified in A. lancea and classified into three groups: Group I (17 members), Group II (33 members), and Group III (15 members). Tissue-specific expression profiling revealed five rhizome-enriched AlWRKY genes (AlWRKY13, AlWRKY20, AlWRKY21, AlWRKY37, and AlWRKY49) were highly expressed in Hubei accessions compared to Jiangsu accessions, and co-expression analysis demonstrated their strong correlation with 16 AlTPS genes. Quantitative PCR (qPCR) validation confirmed the specific upregulation of AlWRKY20, AlWRKY21, AlWRKY37, and AlWRKY49 in Hubei rhizomes, consistent with the accumulation patterns of sesquiterpenes (hinesol, γ-eudesmol, and elemol). Methyl jasmonate (MeJA) induction experiments (12 h) revealed coordinated upregulation of AlWRKY20, AlWRKY37, AlTPS70, AlTPS71, concomitant with significantly increased cis-β-farnesene and α-curcumene content. Molecular docking analysis revealed strong binding affinities of AlWRKY20 to the AlTPS70/AlTPS71 promoter and of AlWRKY37 to the AlTPS70 promoter. Subcellular localization analysis demonstrated that both AlWRKY20 and AlWRKY37 are localized in the nucleus. These results suggest that AlWRKY20 and AlWRKY37 likely function as regulators of sesquiterpene biosynthesis, positively regulating cis-β-farnesene and α-curcumene production through AlTPS gene modulation.DiscussionThis study lays the groundwork for further exploration of the molecular mechanisms and functional validation of WRKY transcription factors in A. lancea.